APPLICATION OF ROLE PLAYING LEARNING METHOD TOWARDS STUDENTS' LEARNING OUTCOMES ON NARRATIVE TEXT MATERIAL IN GRADE IV OF RANTAU PANJANG STATE ELEMENTARY SCHOOL - Utamy, Fera Marlinda; Nurmasyitah, Nurmasyitah; Safiah, Intan (Elementary Education Research, 2025)
This study aims to analyze the application of the Role Playing learning method to student learning outcomes in narrative text material in grade IV of Rantau Panjang State Elementary School. The Role Playing method is a learning strategy that involves students in role-playing activities, so that they can understand the material more interactively and enjoyably. The purpose of the study was to determine the application of the role playing method to student learning outcomes in narrative text material in grade IV at Rantau Panjang State Elementary School, Aceh Tamiang Regency. The approach in this study used a qualitative approach with a descriptive type. This research was conducted at Rantau Panjang State Elementary School. The subjects of this study were all 15 fourth-grade students at Rantau Panjang State Elementary School. Data were obtained through interviews and tests. The results showed that the Role Playing method had a positive impact on student involvement in learning and improved their understanding of narrative text. Students were more enthusiastic and able to compose narrative texts better after participating in learning with this method. These findings indicate that the Role Playing method can be an effective learning strategy in improving student learning outcomes..